Financial Ratios and Earnings Per Share Evidence from Indonesian Food and Beverage Firms - Muhammad Alvin; Fanji Farman (LP2M IAIN Palopo, 2026)
The purpose of this research is to look at food and drink firms listed on the Indonesia Stock Exchange from 2020 to 2024 and see how EPS is affected by current ratios, debt-to-equity ratios, and return on assets. Unpredictability in enterprises' capacity to produce profits for shareholders during the post-pandemic recovery phase prompted the study's impetus. The researchers used panel data regression analysis to take a quantitative approach. There were 121 firm-year observations in the sample, which was comprised of 25 enterprises chosen by selective sampling. Companies' websites and the Indonesia Stock Exchange's published annual financial statements were sources of secondary data. After using the Chow, Hausman, and Lagrange Multiplier tests to pick a model, the Random Effect Model (REM) was determined to have the best fit. Stronger liquidity enables better shareholder profitability, as seen by the positive and substantial influence of Current Ratio on profitability Per Share. A positive and statistically significant relationship between ROA and EPS indicates that efficient use of assets increases profits and value for shareholders. On the other hand, EPS is unaffected by the Debt to Equity Ratio. Return on Assets, Debt to Equity Ratio, and Current Ratio all have a substantial impact on Earnings Per Share at the same time. The significance of profitability and liquidity in enhancing shareholder returns in the food and beverage industry is shown by these studies.